The dual role of TRPV1 in peripheral neuropathic pain: pain switches caused by its sensitization or desensitization - Gao, Ning; Li, Meng; Wang, Weiming; Liu, Zhen; Guo, Yufeng (Frontiers in Molecular Neuroscience, 2024)
The transient receptor potential vanilloid 1 (TRPV1) channel plays a dual role in peripheral neuropathic pain (NeuP) by acting as a “pain switch” through its sensitization and desensitization. Hyperalgesia, commonly resulting from tissue injury or inflammation, involves the sensitization of TRPV1 channels, which modulates sensory transmission from primary afferent nociceptors to spinal dorsal horn neurons. In chemotherapy-induced peripheral neuropathy (CIPN), TRPV1 is implicated in neuropathic pain mechanisms due to its interaction with ion channels, neurotransmitter signaling, and oxidative stress. Sensitization of TRPV1 in dorsal root ganglion neurons contributes to CIPN development, and inhibition of TRPV1 channels can reduce chemotherapy-induced mechanical hypersensitivity. In diabetic peripheral neuropathy (DPN), TRPV1 is involved in pain modulation through pathways including reactive oxygen species and cytokine production. TRPV1’s interaction with TRPA1 channels further influences chronic pain onset and progression. Therapeutically, capsaicin, a TRPV1 agonist, can induce analgesia through receptor desensitization, while TRPV1 antagonists and siRNA targeting TRPV1 show promise in preclinical studies. Cannabinoid modulation of TRPV1 provides another potential pathway for alleviating neuropathic pain. This review summarizes recent preclinical research on TRPV1 in association with peripheral NeuP.